Feasibility Study of the Euphorbia pulcherrima Plant Extract as Natural Dye with Different Mordants for Fabric Dyeing - Bhandari, Netra Lal; Bist, Kabita; Ghimire, Jyoti; Chaudhary, Santosh; Pandey, Durga Prasad; Adhikari, Rameshwar (Journal of Institute of Science and Technology, 2020)
In the present study, an attempt has been made to utilize the natural plant dye extracted from petals of Euphorbia pulcherrima (locally called as Lalupate) via green techniques using water as solvent at boiling condition, for fabrics dyeing in combinations with natural mordants such as Aloe vera, Marcha (traditional yeast used in fermentation), and Chuk (traditional concentrated lemon juice), and artificial mordants like K2Cr2O7, CuSO4, and FeSO4. The dye extract has been characterized by thin-layer chromatography (TLC), ultraviolet-visible (UV-Vis) spectroscopy, Fourier transform infrared (FTIR) spectroscopy, gas chromatography-mass spectrometry (GC-MS) and optical microscopy (OM). The results have shown that the dyeing of the fabrics with the E. pulcherrima dye in combination with K2Cr2O7 as well as Chuk is effective concerning wash fastness, dry fastness, and colorfastness.